Isothermal Crystallization Properties of Polyamide 6 / Hexagonal Boron Nitride Nanocomposites. Issue 1 (2nd January 2018) - Wu, Xiang-Feng; Zhao, Yong-Ke; Li, Xiao-Jun; Wang, Yi-Jin; Zhang, Chen-Xu; Su, Jun-Zhang; Zhang, Jia-Rui; Wang, Kai-Yuan; Wang, Yi-Wei; Zhang, Mi
ABSTRACT: Hexagonal boron nitride was adopted as a heterogeneous nucleation agent to fabricate polyamide 6 based nanocomposite films via a solution casting method. Isothermal crystallization behaviors of the as-prepared films were measured by using differential scanning calorimetry. Results showed that both the crystallization temperature and fillers loading greatly affected the crystallization process of the as-prepared samples. The crystallization nucleation and growth mechanism did not change during the initial stage of crystallization. The halftime of crystallization gradually increased with increasing crystallization temperature. Moreover, it decreased first and then increased with increasing the fillers loading at low crystallization temperature, while it decreased gradually at high crystallization temperature. Furthermore, the crystallization activation energy of the as-prepared samples gradually decreased with increasing fillers loading.